The Influence of Maududi and Jamaat Islami on Sayyid Qutb's Writings - Ali, Nooraihan; HJ Ab Rahman, Asyraf (2012)
One of the most well known scholars in Muslim society of the twentieth century was Sayyid Qutb. Throughout the formative phases of Qutb’s life, many figures were responsible for shaping his cultural and intellectual orientation. This paper will discuss and examine al-Mawdudi’s influence on the life of Sayyid Qutb. The study used content analysis approach by looking into al Mawdudi’s writings and its influence on Sayyid Qutb’s thought manifested through his later writings. Results show that al-Mawdudi was one of the most important figures who responsible for shaping the life of Sayyid Qutb which resulted in profound changes in his intellectual and political outlook as manifested in his writings.